HUBUNGAN KONSUMSI IKAN DENGAN PRESTASI BELAJAR ANAK DI SEKOLAH DASAR SWASTA BRIGJEND KATAMSO II KECAMATAN MEDAN MARELAN KOTA MEDAN - Mentari Christ Riyandini; Etti Sudaryati; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Fish is a source of animal protein that has the advantage is high content of essential fatty acid to help the formation of brain cells in improving the academic achievement of school-age children. In 2013, the average fish consumption rate of the population of Indonesia is still at 35,14 kgs/capita/year. This study aims to determine the relationship of fish consumption with learning achievement in elementary school children of Brigjend Katamso II with a cross-sectional study design and was conducted in November 2013 - August 2014. The study population was all elementary students and samples were taken 68 students with proportional stratified random sampling. Primary data is the identity of respondents, fish consumption, weight and height of children. Secondary data is a general overview of the school and students grades monthly during the second semester of school year 2013/2014. The results showed that the type of fish consumed are marine fish and dairy (48,5%). Sufficient amount of fish consumption (69,1%) with an average of 12,6 g/day. The frequency of fish consumption occasionally (39,7 %) with an average of 4,55 times/week. Learning achievement is very good (57,4%) with an average of 82,67. There is a significant relationship between the amount of fish consumption and learning achievement (p=0,036) and the frequency of fish consumption and learning achievement (p=0,012). Suggested children's fish consumption should be increased quantity and frequency. Learning achievement needs to be maintained. The school is expected to cooperate with the government and deliver nutritional information through the school bulletin. Keywords: Fish Consumption, Learning Achievement